2001
DOI: 10.1021/jf010727m
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neck Region in the Thermal Aggregation of Myosin

Abstract: Carp dorsal myosin formed oligomers that retained ATPase activity upon heating. Cleavage of the oligomeric myosin at subfragment-1 (S-1)/rod junction released monomeric S-1 and rod, indicating that ATPase retaining myosin associated near the S-1/rod junction. The digest also contained rod oligomers. Heating a mixture of S-1 and rod generated neither ATPase retaining S-1 oligomers nor rod oligomers. Electron microscopic observation of the heated myosin revealed that some oligomers were formed by associating at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…S-1 denaturation was much slower than rod denaturation at 0.5 M, which was opposite to the pattern found at 0.1 M. A slow decrease of salt solubility was well correlated to rod denaturation, and ATPase inactivation was explained by S-1 denaturation. As the monomeric myosin content decreased a little faster than S-1 denaturation, myosin formed active aggregates as suggested with carp myosin [13].…”
Section: Thermal Denaturation Of Scallop Myosin When Heated As Dissolmentioning
confidence: 72%
“…S-1 denaturation was much slower than rod denaturation at 0.5 M, which was opposite to the pattern found at 0.1 M. A slow decrease of salt solubility was well correlated to rod denaturation, and ATPase inactivation was explained by S-1 denaturation. As the monomeric myosin content decreased a little faster than S-1 denaturation, myosin formed active aggregates as suggested with carp myosin [13].…”
Section: Thermal Denaturation Of Scallop Myosin When Heated As Dissolmentioning
confidence: 72%
“…Probably great stabilization of S-1 portion by Ca 2+ indirectly affected the denaturation of connecting rod region slightly. It is reported that rod denaturation as studied by aggregate formation was affected by connecting S-1, namely rod aggregates was remarkable when myosin was heated, while no aggregate was formed when S-1 and rod mixture was heated [22]. It was concluded that stabilizing effect of Ca 2+ on myosin is restricted to S-1 portion, and stability of rod portion is primarily unaffected by the presence of Ca 2+ .…”
Section: Discussionmentioning
confidence: 98%
“…This binding formation results in the connection of rod region, creating the network structure of myosin. [6][7][8][9] The myosin solution was incubated at 40 C for 60 min in the absence or presence of AsA, and thehelical contents were compared before and after heating (Fig. 4).…”
Section: )mentioning
confidence: 99%
“…The present results indicate that AsA promotes the thermal gelation of myosin by which the S-1 region is packed via the formation of SS bridges. This binding formation brings out the connection of rod region, creating the network structure of myosin, [6][7][8][9] to become a gel such as heat-induced fish gel. Moreover, it was also confirmed that AsA does not trigger gel formation by bringing about a conformational change in myosin, and that it promotes gel formation according to the mechanism (Fig.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation